TNF-related apoptosis-inducing ligand (TRAIL) for bone sarcoma treatment: Pre-clinical and clinical data. (28th November 2017) - Gamie, Zakareya; Kapriniotis, Konstantinos; Papanikolaou, Dimitra; Haagensen, Emma; Da Conceicao Ribeiro, Ricardo; Dalgarno, Kenneth; Krippner-Heidenreich, Anja; Gerrand, Craig; Tsiridis, Eleftherios; Rankin, Kenneth Samora
Abstract: Bone sarcomas are rare, highly malignant mesenchymal tumours that affect teenagers and young adults, as well as older patients. Despite intensive, multimodal therapy, patients with bone sarcomas have poor 5-year survival, close to 50%, with lack of improvement over recent decades. TNF-related apoptosis-inducing ligand (TRAIL), a member of the tumour necrosis factor (TNF) ligand superfamily (TNFLSF), has been found to induce apoptosis in cancer cells while sparing nontransformed cells, and may therefore offer a promising new approach to treatment. We cover the existing preclinical and clinical evidence about the use of TRAIL and other death receptor agonists in bone sarcoma treatment. In vitro studies indicate that TRAIL and other death receptor agonists are generally potent against bone sarcoma cell lines. Ewing's sarcoma cell lines present the highest sensitivity, whereas osteosarcoma and chondrosarcoma cell lines are considered less sensitive. In vivo studies also demonstrate satisfactory results, especially in Ewing's sarcoma xenograft models. However, the few clinical trials in the literature show only low or moderate efficacy of TRAIL in treating bone sarcoma. Potential strategies to overcome the in vivo resistance reported include co-administration with other drugs and the potential to deliver TRAIL on the surface of primed mesenchymal or immune cells and the use of targeted single chain antibodies such as scFv-scTRAIL. Highlights: TRAIL and other DR4/DR5 agonists are generally potent against bone sarcoma cell lines in vitro and in vivo. Clinical trials in the literature demonstrate only low or moderate efficacy of TRAIL for the treatment bone sarcoma. A potential strategy to overcome toxicity and in vivo resistance involves co-administration with sensitizing agents. TRAIL fusion constructs could improve efficacy by targeting sarcoma specific cell surface proteins. Other approaches have been proposed including the use of mesenchymal stem cells genetically modified to overexpress TRAIL.